1987
DOI: 10.1139/t87-033
|View full text |Cite
|
Sign up to set email alerts
|

Stress release, undrained storage, and reconsolidation in simulated underwater clay

Abstract: Triaxial testing has examined the influence of storage time and reconsolidation procedures on normally consolidated and overconsolidated samples of reconstituted clay prepared with high pore-water pressures to simulate underwater deposits. "Samples" of illite were consolidated one dimensionally, off-loaded without drainage, stored undrained, reconsolidated, and sheared undrained. The storage times were 15 min, I day, and 7 days. Reconsolidation pressures were (1) isotropic to uO,, (2) isotropic to 0.6 u:,,, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
4
3
0
Order By: Relevance
“…Finally, the effect of suction release under an isotropic stress close to the estimated sample suction was investigated. A slight swelling (1.7%) was observed and further compression provided a satisfactory value of the overconsolidation ratio confirming the suggestions of taking some precautions before putting a swelling sample in contact with water as suggested by Graham et al (1987). The various experimental data gathered in this study finally evidenced a relatively good state of conservation of the block sample used.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Finally, the effect of suction release under an isotropic stress close to the estimated sample suction was investigated. A slight swelling (1.7%) was observed and further compression provided a satisfactory value of the overconsolidation ratio confirming the suggestions of taking some precautions before putting a swelling sample in contact with water as suggested by Graham et al (1987). The various experimental data gathered in this study finally evidenced a relatively good state of conservation of the block sample used.…”
supporting
confidence: 83%
“…This swelling is much smaller than that (14%) obtained after saturation at low confining pressure by Coll (2005). Furthermore, the yield stress (p y ') obtained in Figure 8 Horseman et al (1987) cited in Burland (1990) The data of the test of Figure 8 confirm, as suggested by Graham et al (1987), that some precautions have to be taken before releasing the suction of a natural sample. Note however that the slight swelling observed during the test indicate that the initial suction might be higher than 2.5 MPa.…”
Section: Suction Release Under Isotropic Stresssupporting
confidence: 60%
See 1 more Smart Citation
“…It was found that the discrepancy between UU and CAUC test results increased with increasing storage time. Kirkpatrick et al (1986), Graham et al (1987), Graham and Lau (1988) and Graham et al (1990) extended the above study to overconsolidated kaolin and illite, "underwater" samples of illite, "underwater" samples of grundite and to illite respectively and found more or less the same results, all stressing in particular the importance of anisotropic consolidation prior to shearing. Numerous other studies have demonstrated the inadequacy of the UU test for the measurement of in situ strength.…”
Section: Impact On Mechanical Propertiesmentioning
confidence: 72%
“…During the loaded-swell tests, the specimens were reloaded to its overburden stress (path D-C) and then flooded to swell (path C-E-F). When performing triaxial tests on soil specimens taken from great depth, Delage et al (2007), Graham et al (1987) applied the "in-situ" stress prior to re-saturate the soil. This procedure avoids the large soil swelling which may induce a microstructure change, resulting in a modification in mechanical behaviour.…”
Section: Discussionmentioning
confidence: 99%